PERBANDINGAN PEMBELAJARAN KOOPERATIF TIPE STRUCTURED NUMBERED HEADS (SNH) DAN NUMBERED HEAD TOGETHER (NHT) TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS X MIPA SMAN 6 KOTA BENGKULU - Evi Elyani; Sumpono Sumpono; Hermansyah Amir (ALOTROP, 2019)
The purpose of this research is to measuring the comparison of students creative thinking ability between cooperative learning model type Stuctured Numbered Heads (SNH) and Numbered Head Together (NHT) on nomenclatur of chemical compounds material in curriculum 2013 of grade X MIPA SMA Negeri 6 Bengkulu city school year 2017/2018. This research is a quasi-experimental research with total population 118 students and sample 57 students with class X MIPA D as experiment class I that apply cooperative learning model type SNH and class X MIPA B as experiment class II applying cooperative learning model type NHT. Analysis of the data used are mean values, Percentage Indicator, normality test, homogeneity test, and hypothesis test (t test). The students' creative thinking ability in this study is seen from the difference between pretest and posttest. In the experimental class I, the average value of students creative thinking ability was 51,851 while the experimental class II was 46,916. The result of t test (? = 0,05) obtained tcount> ttable is 2,645> 2,0040 indicates the accepted hypothesis  means that there is a significant difference between students' creative thinking ability using cooperative learning model type SNH and NHT, where the model of cooperative learning type SNH is more influential on students’ creative thinking ability compared with cooperative learning type model NHT.